Erdheim-Chester Disease: A Case Report and Review of the Literature - Merai, Hema; Collas, David; Bhagat, Ashish; Mandalia, Uday (Journal of Clinical Imaging Science)
Erdheim-Chester disease (ECD) is a rare form of non-Langerhans’ cell histiocytosis characterized by xanthogranulomatous infiltration of foamy histiocytes surrounded by fibrosis. ECD may be asymptomatic or present as a multi-systemic disease with life-threatening manifestations, most commonly involving the skeletal system. Immunohistochemical staining demonstrates cells that are CD68+, CD1a–, and S100– with an absence of Birbeck granules. We report a case of a 69-year old male patient who presented with neurological symptoms – eventually thought to be separate to his diagnosis of ECD. It represents the ability to diagnose ECD based just on radiological findings in an otherwise asymptomatic individual.